STANDARISASI PENDIDIKAN, PROFESIONALISME GURU, KOMPETENSI LULUSAN DAN DAMPAK TERHADAP KEPUASAN PELANGGAN SEKOLAH - Jentot T; Heris H; Janaenah Janaenah; Sopyan Sauri; Ujang Cepi Barlian (Eduvis : Jurnal Manajemen Pendidikan Islam, 2022)
National Education Standards as Indicators of school customer satisfaction based on objectives, principles, and types of services. Teachers as professionals function to improve the quality of national education. Teachers influence the creation of quality educational processes and outcomes. Teaching productivity is a mental attitude that is always looking for improvements to what already exists in the context of teaching will affect the academic and moral quality of students. Teacher professionalism, teaching motivation and participatory leadership of school principals each have a relationship with teaching productivity. So that the competence of graduates has a significant relationship with student achievement which can provide the maximum level of satisfaction for schools. This study uses qualitative methods through analysis of literature obtained from books, journals and other relevant sources. The results of this study indicate that this National Education Standard must be met for all educational institutions that run or provide education throughout Indonesia. This teacher professionalism is closely related to the teacher's role in the teaching (pedagogical) field, so that teachers need pedagogical knowledge and skills to support an effective teaching and learning process and will have an impact on the skills and competencies of graduates. The school management service principle demonstrates the school's strong interest in making it the standard. Indicators of the types of school management services in providing customer satisfaction include various activities carried out through program planning, program implementation, program evaluation, and program follow-up at the educational institution itself. ABSTRAK Standar Nasional Pendidikan sebagai Indikator terhadap kepuasan pelanggan sekolah yang didasarkan pada tujuan, prinsip, dan jenis layanan. Guru sebagai tenaga profesional berfungsi meningkatkan mutu pendidikan nasional. Guru mempengaruhi terciptanya proses dan hasil pendidikan yang berkualitas. Produktivitas mengajar merupakan sikap mental yang selalu mencari perbaikan terhadap apa yang telah ada dalam konteks mengajar akan mempengaruhi kualitas akademik maupun moral peserta didik . Profesionalisme guru, motivasi mengajar dan kepemimpinan partisipatif kepala sekolah masing-masing memiliki hubungan terhadap produktivitas mengajar. Sehingga kompetensi lulusan memiliki hubungan yang signifikan dengan prestasi belajar siswa yang dapat memberikan tingkat kepuasan yang maksimal bagi sekolah. Penelitian ini menggunakan metode kualitatif melalui analisis literatur yang didapatkan baik dari buku, jurnal dan sumber lainnya yang relevan. Hasil penelitian ini menunjukan bahwa Standar Nasional Pendidikan ini harus dipenuhi bagi semua lembaga pendidikan yang menjalankan atau menyelenggarakan pendidikan di seluruh Indonesia. Profesionalisme guru ini sangat berkaitan dengan peran guru dalam bidang pengajaran (pedagogis), sehingga guru memerlukan pengetahuan dan keterampilan pedagogis untuk mendukung dalam proses belajar mengajar yang efektif dan akan berdampak terhadap keahlian dan kompetensi lulusan. Prinsip layanan manajemen sekolah menunjukkan kepentingan kuat sekolah menjadikannya sebagai standar. Indikator jenis layanan manajemen sekolah dalam memberikan kepuasan pelanggan meliputi berbagai kegiatan yang dilakukan melalui perencanaan program, pelaksanaan program, evaluasi program, dan tindak lanjut program di lembaga pendidikan itu sendiri.